Óleo diesel/ tensoativo não iônico/ água: comportamento de fases - Celedonio, Wirly Maria Lemos (Universidade Federal Rural do Semi-Árido, 2018)
Over the years, increased demand for clean and efficient non-oil fuels has become noticeable due to the increase in global pollution and a consequent increase in global warming caused by the burning of hydrocarbon fuel as also due to the oil reserves having a finite life. Despite the efforts also made in the mechanics of diesel engines, they are still large polluters, mainly soot and gases such as carbon monoxide, sulfur oxides and nitrogen oxides and hydrocarbons. Therefore, studies have been carried out to replace these fuels with several other types such as: biodisel, diesel / biodiesel blends, ethanol / diesel blends, emuticated and microemulsified fuels. The present study will have the purpose of obtaining ternary diesel / surfactant / water diagrams targeting a region of microemulsion for use as fuel in compression ignition engines.
Monografia
Keywords: Microemulsão; Diesel; Diagrama de fases; Microemulsion; Diesel; Ternary diagram; ENGENHEARIAS::ENGENHARIA QUIMICA